The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.physleta.2016.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and resonance properties of the Smilansky Hamiltonian

Abstract: We analyze the Hamiltonian proposed by Smilansky to describe irreversible dynamics in quantum graphs and studied further by Solomyak and others. We derive a weak-coupling asymptotics of the ground state and add new insights by finding the discrete spectrum numerically. Furthermore, we show that the model has a rich resonance structure.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…We are not going to give proofs of these claims referring to the papers quoted above, instead we will show how the the discrete spectrum can be found numerically following [10] which can provide additional insights. At the time, however, the method we use, rephrasing the task as a spectral problem for Jacobi matrices is the core of the proofs done by Solomyak et al providing thus a feeling of what is the technique involved.…”
Section: Smilansky-solomyak Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not going to give proofs of these claims referring to the papers quoted above, instead we will show how the the discrete spectrum can be found numerically following [10] which can provide additional insights. At the time, however, the method we use, rephrasing the task as a spectral problem for Jacobi matrices is the core of the proofs done by Solomyak et al providing thus a feeling of what is the technique involved.…”
Section: Smilansky-solomyak Modelmentioning
confidence: 99%
“…The models we consider have other interesting properties. Let us return to the setting of Section 2 and show that the system exhibits a rich resonance structure; we refer to [10,11] for a detailed discussion of these phenomena. To begin with, we have to say which resonances we speak about.…”
Section: Resonances In Smilansky-solomyak Modelmentioning
confidence: 99%
“…The asymptotic expansion of this eigenvalue Λ 1 can be found by an argument similar to that used in [14] for the original Smilansky model. The system of equations (14) can be after substitution Q n = (n + 1 2 ) 1/4 C n rewritten as…”
Section: Discrete Spectrum Of H βmentioning
confidence: 99%
“…The affirmative answer was provided in [11] where such a potential family was constructed, in [12] it was demonstrated that the effect persists even if the system is exposed to a homogeneous magnetic field (in which case the original Smilansky interpretation is ultimately lost). Moreover, it was shown that the original model has a rich resonance structure [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…While this is all true in many cases, it need not be true in general. This was demonstrated by Uzy Smilansky using a simple model [Sm04] which was subsequently analyzed in detail and generalized by Mikhail Solomyak and coauthors [So04a,So04b,ES05a,ES05b,So06a,So06b,NS06,RS07], see also [Gu11] and [ELT17].…”
Section: Introductionmentioning
confidence: 95%